Sacrococcygeal teratoma with yolk sac elements (endodermal sinus tumors) in two years old child - Talal, Lubab F.; Khalid, Enam A. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Sacrococcygeal teratoma is seen in 1 in every 35000 live births, and is the most common tumor presenting in newborn and children but also reported in adults.(1)Sacrococcygeal teratoma are the most common type of germ cell tumors (both benign and malignant) diagnosed in neonates , infants and children younger than 4 years.(2)Case report: A 2 years old male child presented with a visible lump or mass under the skin at the top of the buttocks crease after falling on the ground on his buttocks, and the parents give a history that the child had a constipation since birth. The case was diagnosed as endodermal sinus tumor with yolk sac elements on the bases of clinical examination, ultrasonography, CTscan and fine-needle aspiration cytology. After diagnoses patient referred to the oncologist for multi-drug chemotherapy and surgical removalby the pediatric surgeon after shrinkage of the tumor mass.Conclusion: Infants and young children present with a palpable mass in the sacropelvic region have a greater likelihood of being malignant.